Fundamentos filosóficos da semântica argumentativa : um legado de Platão à linguística - Rocha, Thomas (2016)
This work aims to address the nexus between the theory of alterity developed by Plato in his Sophist dialogue and the theory of linguistic value introduced by Ferdinand de Saussure in his Course in General Linguistics (CGL). It departs from the hypothesis raised by Oswald Ducrot that Saussure, by developing the notion of linguistic value, applies in the study of language what Plato stated about ideas. Ducrot – an expert in classical philosophy – draws in the linguistic value theory to develop the branch in linguistic studies known as Argumentative Semantics. According to Ducrot, it is possible to find the philosophical origin of Saussure's theory of value in Plato's theory of alterity. The article intends to draw on a detailed study on the dialogue between Sophist and CGL to circumscribe concepts belonging to different fields of study: philosophy and linguistics. Thus, it aims an epistemological perspective. By the means of the aforementioned works, Ducrot set a nexus between the idea of alterity and the notion of value by finding in both the idea of “opposition” as constitutive of the issues under analysis. Through the investigation and the deepening of the understanding on the notion of value, it tries to reveal the philosophical influences under the concept developed by the Genebrian linguist. Both Plato and Saussure have set discourses which echo in posterity. These discourses are texts dialoguing with the theories they help to build. In this regard, it looks to counterpoint their interdiscursivity.